Interpretation of the mechanism of acetylcholinesterase inhibition ability by organophosphorus compounds through a new conformational descriptor. an experimental and theoretical study - Mastrantonio Garrido, Guido Enrique (2008)
Organophosphorus pesticides are the most common classes involved in poisonings related to pesticides. We used inhibitory ability on enzymatic activity of acetylcholinesterase activity and molecular mechanics or ab initio methods of molecular modelling to perform a theoretical approach of the enzyme interaction mechanism of these compounds. Kinetic values for strong and weak inhibitors were measured in a high amplitude range for affinity (Kₐ) and phosphorylation constants (Kₚ). To quantitatively describe the conformational behaviour of these molecules, conformational descriptors of free molecules were developed. Quantitative structure activity relationships (QSARs) were constructed with inhibition kinetic values and their molecular descriptors. The conformational descriptors show a high degree of correlation with the kinetic behaviour of these molecules. A positive correlation between the conformational freedom of the studied molecules with Kₐ is observed. This study allows us to reinterpret the organophosphorus cholinesterase inhibition mechanism and consequently the ‘thiono’ and ‘thiolo effect’ based on a global ‘chalcogen effect’.